2003
DOI: 10.1186/1475-9276-2-7
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in under-five child malnutrition in South Africa

Abstract: Objectives: To assess and quantify the magnitude of inequalities in under-five child malnutrition, particularly those ascribable to socio-economic status and to consider the policy implications of these findings.Methods: Data on 3765 under-five children were derived from the Living Standards and Development Survey. Household income, proxied by per capita household expenditure, was used as the main indicator of socio-economic status. Socio-economic inequality in malnutrition (stunting, underweight and wasting) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
184
2
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(217 citation statements)
references
References 17 publications
29
184
2
2
Order By: Relevance
“…Moreover, hunger and food insecurity affected about 50 % and 25 % of households, respectively, in 1999 (2) . Similar findings have been reported in smaller studies conducted in various regions of the country (4,5) . To combat vitamin A deficiency, a curative vitamin A supplementation protocol was implemented in the Western Cape Province targeting high-risk mothers and children.…”
supporting
confidence: 79%
“…Moreover, hunger and food insecurity affected about 50 % and 25 % of households, respectively, in 1999 (2) . Similar findings have been reported in smaller studies conducted in various regions of the country (4,5) . To combat vitamin A deficiency, a curative vitamin A supplementation protocol was implemented in the Western Cape Province targeting high-risk mothers and children.…”
supporting
confidence: 79%
“…The wide variation in South African prevalence rates is possibly due to inequalities in socio-economic status, since it has been shown that some provinces, including Limpopo, are amongst the poorest. Limpopo Province has a high prevalence of illiteracy, high rates of unemployment, poor sanitation facilities, low levels of electrification and high household density, which have all been documented as being related to stunting 35 . Previous research has shown that overweight is an outcome of sociodemographic status, maternal feeding practices and cultural beliefs as to what is normal 1,9,36 -39 .…”
Section: Discussionmentioning
confidence: 99%
“…Child undernutrition is one of the measures of health status that the World Health Organization (WHO) recommends for equity in health 2 . Conversely, undernutrition has been estimated to be an underlying cause for around half of all child deaths worldwide 3 .…”
Section: Introductionmentioning
confidence: 99%